Development Module Based QR Code Utilization in Field Practices Invertebrates Zoology Course - Andi Badli Rompegading; Devi Wulandari Ramli; Muhammad Nur; Rizal Irfandi (Postgraduate, University of Mataram, 2023)
This study aims to develop a QR Code-based module in its use in the field practicum of invertebrate species in the Invertebrate Zoology course in the form of the Invertebrate Zoology module. This type of research is development research using the ADDIE model. The research procedure consists of 5 stages, namely analysis, design, development, implementation, and evaluation. In this study, an assessment of the use of modules as learning media was used, the instruments used in the study were material validation questionnaires, media validation, practicality questionnaires, and student response questionnaires. The data collected were analyzed quantitatively and qualitatively. The results showed that the QR Code-based module on invertebrate species material in its use in the field practicum of the Invertebrate Zoology course was feasible to use based on the assessment of material I experts as much as 88% and material II experts as much as 80% and media experts 88.5% with a very valid category. , and 80% practicality data and 85% student response questionnaire. The development of learning media based on QR Code for Invertebrate species material in its use in the field practicum for the Invertebrate Zoology course is feasible to be used as a support for learning in the Invertebrate Zoology course